If $\sum_{k=1}^{\infty}x_k$ is conditionally convergent, prove that $\sum_{k=1}^{\infty}x_k^+ = \infty = \sum_{k=1}^{\infty}x_k^-$ where $x_k^+$ are the positive terms and $x_k^-$ are the absolute values of negative terms of $x_k$.

Proof: Suppose $x_k$ is only conditionally summable, this means that the sequence $s_n = \sum\limits_{k=1}^{n}|x_k|$ is not convergent. Note that $s_n$ is a monotone increasing sequence that is not convergent, hence it must be unbounded. But $\sigma_n^+ = \sum\limits_{k=1}^{n}x_k^+$ and $\sigma_n^- = \sum\limits_{k=1}^{n}x_k^-$ are all subsequences of $s_n$, and they are monotone increasing as well.

Thus, they must me also unbounded and $\sum\limits_{k=1}^{\infty}x_k^+ = \infty = \sum\limits_{k=1}^{\infty}x_k^-$. $\blacksquare$

EDIT: Here's my another attempt at proving this:

Proof: Note that $s_n = \sum_{k=1}^{n}|x_k|$ is divergent to $\infty$. But $s_n' = \sum_{k=1}^{n}x_k$ converges to some finite number $L\in\mathbb{R}$. Let $\sigma_n^+ = \sum\limits_{k=1}^{n}x_k^+$ and $\sigma_n^- = \sum\limits_{k=1}^{n}x_k^-$. Then, $s_n = \sigma_n^+ + \sigma_n^- $ and $s_n' = \sigma_n^+ - \sigma_n^-$. Then, $s_n+s_n' = 2\sigma_n^+$ must diverge to infinity as $n\to\infty$ because $s_n$ diverges to $\infty$ and $s_n'$ converge to $L$. Any finite number added to infinity is also infinity. This implies that $2\sigma_n^+$ must diverge as well as $\sigma_n^+$.

Likewise, $s_n'-s_n = -2\sigma_n^-$ must diverge to $-\infty.$ And this implies $-2\sigma_n^-$ diverge to $-\infty$ and $\sigma_n^-$ diverges to $\infty$. $\blacksquare$

  • 2
    $\begingroup$ Are you taking the absolute value of the negative terms? Otherwise, $\sum x_k^- = - \infty$. $\endgroup$ – Alexis Olson Mar 8 '17 at 19:47
  • $\begingroup$ Yes, I forgot to mention that $x_k^-$ has to be absolute value of the negative terms of $x_k.$ $\endgroup$ – user3000482 Mar 8 '17 at 19:48
  • 2
    $\begingroup$ $\sigma_n^+$ and $\sigma_n^-$ are not subsequences of $s_n$. But your consideration on those partial sums is indeed a good beginning. As a possible angle of attack, you may utilize the relation $$s_n = \sigma_n^+ + \sigma_n^- \qquad \text{and} \qquad \sum_{k=1}^{n} x_k = \sigma_n^+ - \sigma_n^-$$ to reach the conclusion. $\endgroup$ – Sangchul Lee Mar 8 '17 at 19:49
  • 1
    $\begingroup$ $\sigma_n^{\pm}$ are obtained by summing certain portion of summands of $s_n$. In other words, they may be understood as partial sums for certain subsequences of $|x_k|$'s. This is not the same as picking certain terms in the sequence $(s_n)$. Let me see if I can devise a simple example that easily demonstrates this difference. $\endgroup$ – Sangchul Lee Mar 8 '17 at 19:56
  • 3
    $\begingroup$ Shorter argument: since the sequence is not absolutely summable, one of the two has to diverge; if only one diverged then the whole thing wouldn't be convergent. $\endgroup$ – Ian Mar 8 '17 at 20:51

Notice $x_k^{+} = x_k$ if $x_k \geq 0$, and $x_k^{+}=0$ otherwise. Notice $x_k^{-} = -x_k$ if $x_k \leq 0$, and $x_k^{-}=0$ otherwise.

Put $$s_n = \sum_{k=1}^{n} |x_k|, \quad \sigma_n = \sum_{k=1}^{n} x_k, \quad \sigma_n^{+} = \sum_{k=1}^{n} x_k^{+}, \quad \sigma_n^{-} = \sum_{k=1}^{n} x_k^{-}. $$ Note $$\sigma_n^{+} = \frac{1}{2}s_n + \frac{1}{2}\sigma_n.$$ Since $s_n$ diverges and $\sigma_n$ converges, we must have that $\sigma_n^{+}$ diverges. Moreover, as $\sigma_n^{+}$ is increasing, $\sigma_n^{+} \rightarrow \infty$.

Likewise, $\sigma_n^{-} = \frac{1}{2}s_n - \frac{1}{2}\sigma_n$ leads to $\sigma_n^{-} \rightarrow \infty$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.